Evaluation and comparison of control and heat treated l-shape furniture joints produced from scotch pine and ash wood under static bending and cyclic fatigue bending loadings - Demirel, Samet; Sener, Ruveyda (Maderas. Ciencia y Tecnología, 2022)
This study investigated how the mechanical properties of L-shape joints produced from heat treated Scotch pine or ash wood behaved under cyclic fatigue loading and compared this with the mechanical properties of non-heat treated wood materials. Additionally, static bending performances of the L-shape of joints were investigated and compared to fatigue bending performance of same type of joints. Results indicated that increasing number of staple from 6 to 8 and density generally increased static bending of L-shape joints. Static bending resistance of L-shape joints produced from control Ash wood significantly higher than those of L-shape joints produced from heat treated Ash wood while no significant difference were observed between static bending resistance L-shape joints produced from control Scotch pine and L-shape joints produced from heat treated Scotch pine wood. The fatigue bending resistances of L-shape joints produced from heat treated samples generally passed and failed the same loading steps with those produced from control samples which means both L-shape joints could be used in same service area. L-shape joints under static and fatigue loadings mostly indicated staple leg shear mode. The one under fatigue loading was more than the one under static loading. Additionally, some joints under fatigue loading indicated staple rupture. The overall ratio of static bending loading to cyclic fatigue bending loading for L-shape joints was obtained as 2.85.